BOOK COLLECTIONS IN CORPORE IN LITHUANIAN LIBRARIES - BRAZIŪNIENĖ, ALMA (Knygotyra, 2013)
A book collection in corpore is usually used to describe a historically formed, indivisible collection of books having a historic, scientific and cultural value. Specialized research on this topic in Lithuania has been scanty, if any, with the exception of research conducted on acquiring and storing book collections in libraries as well as similar topics. The article aims at investigating the theoretical aspects of using the term book collection and providing the analysis of existing practices and trends with regard to book collections both in Lithuanian and foreign libraries. To achieve this objective, the following methods of literary analysis and empirical research have been used: analysis of library websites, expert survey, interviews with the library staff taking care of book collections at their disposal. The objects of research are the book collections in corpore, acquired and stored in the National Library of Lithuania, libraries of state-level and county libraries. The libraries which decide to store and preserve book collections in corpore, undertake a museum function, that is, the inherent function pertinent to a memory institution. This function is not characteristic of public libraries. However, it is among the core functions of the libraries having the national and state status. Based on the criterion of the former owner, collections in corpore can be grouped as follows: personal libraries (the libraries of outstanding statesmen, public figures, science and culture makers) and book heritage of various institutions (institutional libraries). It turned out that currently 144 collections in corpore are being stored in the National Library of Lithuania, state-level and county libraries, with personal libraries identified as the prevailing group among them (137). The seven remaining collections in corpore are institutional libraries. The analysis of the information available in library websites on the collections in corpore revealed that the material presented is rather scarce and the websites do not contain comprehensive information about the scope of the respective collections. Thus, the user’s access to information is rather restricted. Today, the acquisition of collections in corpore has been reduced in scope, reflecting the current situation in librarianship. The status of some of the libraries which have acquired a great many book collections in corpore (for example, Vilnius University Library) have to be reviewed. Having established whether we are dealing with a collection in corpore or whether it is merely a donated collection of books, we can integrate the books in question into the library holdings, marking book provenance indicators in a bibliographic description in the online catalogue. Due to their exclusivity, book collections in corpore are becoming book monuments. Such a status puts their custodians under an obligation to treat them as the sets of documents having special value, that is, as book monuments.